Criminal Law - Open Textbook Library (Open Textbook Library, 2015)
Criminal Law uses a two-step process to augment learning, called the applied approach. First, after building a strong foundation from scratch, Criminal Law introduces you to crimes and defenses that have been broken down into separate components. It is so much easier to memorize and comprehend the subject matter when it is simplified this way. However, becoming proficient in the law takes more than just memorization. You must be trained to take the laws you have studied and apply them to various fact patterns. Most students are expected to do this automatically, but application must be seen, experienced, and practiced before it comes naturally. Thus the second step of the applied approach is reviewing examples of the application of law to facts after dissecting and analyzing each legal concept. Some of the examples come from cases, and some are purely fictional. All the examples are memorable, even quirky, so they will stick in your mind and be available when you need them the most (like during an exam). After a few chapters, you will notice that you no longer obsess over an explanation that doesn't completely make sense the first time you read it-you will just skip to the example. The examples clarify the principles for you, lightening the workload significantly.
Chapter 1: Introduction to Criminal Law -- Chapter 2: The Legal System in the United States -- Chapter 3: Constitutional Protections -- Chapter 4: The Elements of a Crime -- Chapter 5: Criminal Defenses, Part 1 -- Chapter 6: Criminal Defenses, Part 2 -- Chapter 7: Parties to Crime -- Chapter 8: Inchoate Offenses -- Chapter 9: Criminal Homicide -- Chapter 10: Sex Offenses and Crimes Involving Force, Fear, and Physical Restraint -- Chapter 11: Crimes against Property -- Chapter 12: Crimes against the Public -- Chapter 13: Crimes against the Government -- Chapter 14: Appendix A: Case Listings
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States